2007
DOI: 10.1557/jmr.2007.0437
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of CuAlO2thin film electrical conduction by the anisotropic conductivity

Abstract: CuAlO2 thin films with (015) preferential orientation growth have been synthesized on quartz substrates using radio frequency (rf) magnetron sputtering at low temperature. Via the optimized postannealing condition (in N2 preserved ambient at 900 °C for 5 h), the preferential orientation of the films changes from (015) to (001) direction. The use of a higher conductivity at the ab plane of CuAlO2 compared with that along the c axis, reduces the resistivity of the film at room temperature to 37 Ω·cm from that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Thus, it seems that the (0 0 l) preferred orientation is the dominant factor with responsibility for the increase of the Hall mobility and then for the increase of the electrical conductivity with decreasing P W . In our previous paper [22], the hole carrier concentration and Hall mobility are calculated to be around 3.40 Â 10 16 cm À3 and 4.07 cm 2 V À1 s À1 , respectively, which are basically consistent with the results of this work.…”
Section: The Electrical Properties Of Cualo 2 Thin Films With Differesupporting
confidence: 90%
See 3 more Smart Citations
“…Thus, it seems that the (0 0 l) preferred orientation is the dominant factor with responsibility for the increase of the Hall mobility and then for the increase of the electrical conductivity with decreasing P W . In our previous paper [22], the hole carrier concentration and Hall mobility are calculated to be around 3.40 Â 10 16 cm À3 and 4.07 cm 2 V À1 s À1 , respectively, which are basically consistent with the results of this work.…”
Section: The Electrical Properties Of Cualo 2 Thin Films With Differesupporting
confidence: 90%
“…Under the lower P W , the stronger bombardments by higher energetic particles to the substrate surface produce more pits, which increase the nucleation sites. The growth of nuclei along (0 0 l) orientation is much faster than ones along other directions, by which the system has lower energy [22]. It was already reported that the electrical property of CuAlO 2 thin film is anisotropic [22,23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…were prepared, respectively. After the deposition, all the asprepared films were annealed at 900°C for 5 h in N 2 , the annealing condition had been studied previously [19,20].…”
Section: Methodsmentioning
confidence: 99%